Pattern synthesis using combination of the induced EMF method and a genetic algorithm - Abdul Malek, Norun; Seager, Rob; Flint, James (2011)
This paper presented pattern synthesis using the Induced EMF Method and a Genetic Algorithm (GA). A cosine shaped main beam has been chosen as desired pattern. This technique is suitable for 3D antenna arrays where the position of each element is in various configurations. For 700 generations and penalty constant is 0.05, the GA converges rapidly until it reaches 200 and remains constant at 0.79. This value represents the comparison between desired and optimised radiation pattern.